Acoustic, perceptual and clinical correlates of speech and voice in isolated dystonia: Preliminary findings. Issue 6 (12th August 2021) - Cuartero, Marie‐Charlotte; Bertrand, Roxane; Rauzy, Stéphane; Véron‐Delor, Lauriane; Atkinson‐Clement, Cyril; Grabli, David; Vidailhet, Marie; Pinto, Serge
Abstract: Background: Hyperkinetic dysarthria is often present in isolated dystonia (ID) and is still understudied. Four main clusters of deviant speech dimensions in dystonia hyperkinetic dysarthria were initially provided: articulatory inaccuracy, phonatory stenosis, prosodic excess and prosodic insufficiency. Aim: The aim of our exploratory study was to provide preliminary data on both perceptual and acoustic analyses in relation to three out of these four main clusters. Methods & Procedures: Eleven patients with ID and 11 healthy controls (HC) participated in this study. Clinical/perceptual assessments and acoustic analyses of speech recordings were performed, the latter allowing for the analysis of parameters referring to aerophonatory control, voice quality, prosodic features and speech intelligibility estimated by nine listeners. Between‐group statistical comparisons were performed (Wilcoxon tests, p < 0.05). Single‐case differences between each patient and the control group were also carried out (effect size index and t < 0.05). Outcomes & Results: Between‐group comparisons confirmed the presence of a 'phonatory stenosis'; in addition, deficit in aerophonatory control and hypophonia was also displayed. 'Prosodic insufficiency' was confirmed, but not at the individual level. 'Prosodic excess' manifested only in patients with marked and severe dysarthria. Correlations between altered maximum phonation time, loudness variation, speech and articulatory rates on the one hand, and several clinical speech assessments on the other hand, were also found. Conclusions & Implications: From these findings, altogether, perceptual characteristics of hyperkinetic dysarthria, as suggested by Darley et al., were quantified by the acoustic parameters we measured. As regards to our data obtained in a small participant sample, we would suggest that Darley et al.'s clusters of excess and insufficiency prosody should be questioned in future studies involving larger numbers of dystonic patients. Our study provides novel and preliminary results that demonstrate the relevance of using quantitative measures to further characterise speech/voice deficits in patients with ID.